Chemical and structural studies provide a mechanistic basis for recognition of the MYC G-quadruplex. Issue 1 (December 2018) - Calabrese, David; Chen, Xiang; Leon, Elena C.; Gaikwad, Snehal M.; Phyo, Zaw; Hewitt, William; Alden, Stephanie; Hilimire, Thomas; He, Fahu; Michalowski, Aleksandra; Simmons, John; Saunders, Lindsey; et al.
Abstract G-quadruplexes (G4s) are noncanonical DNA structures that frequently occur in the promoter regions of oncogenes, such asMYC, and regulate gene expression. Although G4s are attractive therapeutic targets, ligands capable of discriminating between different G4 structures are rare. Here, we describe DC-34, a small molecule that potently downregulatesMYC transcription in cancer cells by a G4-dependent mechanism. Inhibition by DC-34 is significantly greater forMYC than other G4-driven genes. We use chemical, biophysical, biological, and structural studies to demonstrate a molecular rationale for the recognition of theMYC G4. We solve the structure of theMYC G4 in complex with DC-34 by NMR spectroscopy and illustrate specific contacts responsible for affinity and selectivity. Modification of DC-34 reveals features required for G4 affinity, biological activity, and validates the derived NMR structure. This work advances the design of quadruplex-interacting small molecules to control gene expression in therapeutic areas such as cancer. Targeting noncoding nucleic acids with small molecules represents an important and significant challenge in chemical biology and drug discovery. Here the authors characterize DC-34, a small molecule that exhibits selective binding to specific G4 structures, and provide a structural basis for its selectivity